2020
DOI: 10.6018/analesps.394021
|View full text |Cite
|
Sign up to set email alerts
|

Factorial analysis and invariance by sex and age of the Anger Rumination Scale ARS Spanish version

Abstract: La rumiación ira es pensamiento perseverativo sobre un evento personalmente significativo ocurrido a la persona o las demás que conlleva a la ira y se constituye como factor de riesgo para la agresión. El objetivo fue realizar un análisis factorial confirmatorio e invarianza por sexo y edades de la Anger Rumination Scale [ARS]. Se conformó una muestra no probabilística de 640 personas con entre 18 y 63 años (M = 31.07, SD = 11.27), agrupadas por sexos (252 hombres, 378 mujeres) y edades (278 menores de 25 años… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…The analyses of measurement invariance by gender, age group (≤ 25 and ≥ 25 years) and sample type (community vs. clinical sample) showed a total con gural, metric and strict invariance for gender and age group that was consistent with a previous study of the ARS with four factors (Toro et al, 2020) and for the community vs. clinical sample. However, the three-factor structure of this study showed the greatest parsimony and was the most consistent and feasible one from a conceptual and methodological point of view.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The analyses of measurement invariance by gender, age group (≤ 25 and ≥ 25 years) and sample type (community vs. clinical sample) showed a total con gural, metric and strict invariance for gender and age group that was consistent with a previous study of the ARS with four factors (Toro et al, 2020) and for the community vs. clinical sample. However, the three-factor structure of this study showed the greatest parsimony and was the most consistent and feasible one from a conceptual and methodological point of view.…”
Section: Discussionsupporting
confidence: 86%
“…This structure has been replicated in several countries including Brazil, the United Kingdom and Hong Kong, France, Spain, Australia-Spain, Turkey, Iran, and Colombia (Besharat, 2011 The studies reviewed suggest that the ARS has good structural validity. However, we consider that those studies have some shortcomings, in particular: 1) Although most studies have focused on the relationship between anger rumination and aggression (Magán et al, 2016;Ortega-Andrade et al, 2017;Ramos-Cejudo et al, 2017;Toro et al, 2020), few studies have associated anger rumination with anxiety and depression symptoms, at least at the predictive level. 2) Very few studies included an analysis of factorial invariance by gender, age group and with a community sample vs. a clinical sample.…”
Section: Introductionmentioning
confidence: 99%
“…Anger rumination was measured using the Anger Rumination Scale (Sukhodolsky et al, 2001; validated in Spanish by Toro et al, 2020), composed of 19 Likert-type items on a scale of 1-4 (1 = Hardly ever; 4 = Nearly always), to assess the tendency to think about situations that lead to anger, to remember past episodes of anger and to dwell on the causes and consequences of episodes of anger. Example item: I dwell on my past experiences of anger.…”
Section: Instrumentsmentioning
confidence: 99%
“…The dimensionality of the ARS has been examined in different cross-cultural settings: Iran (Besharat, 2011), Hong Kong, and Great Britain (Maxwell, 2004; Maxwell et al, 2005), Australia and Spain (Ramos-Cejudo et al, 2017), Colombia (Toro et al, 2020), France (Reynes et al, 2013), Turkey (Satici, 2014), Mexico (Ortega-Andrade et al, 2017), and Spain (Uceda et al, 2016). All but one studies (Maxwell, 2004) have confirmed the hypothesized four-factor structure of the inventory proposed by Sukhodolsky et al (2001).…”
mentioning
confidence: 99%